2015
DOI: 10.5214/ans.0972.7531.220204
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of risk factors, outcome and biomarker levels in young and old acute ischemic stroke patients

Abstract: BackgroundStroke is the third leading cause of death and disability worldwide accounting for 400-800 strokes per 100,000 individuals each year.PurposeIn the present study, we compared risk factors, clinical outcome, and prognostic biomarkers NSE, S-100 ßß and ITIH4 levels in young and old acute ischemic stroke (AIS) patients.MethodsWe compared the risk factors and clinical outcomes in young (n = 38) and old (n = 66) AIS patients admitted to tertiary health care centre in Central India. In addition, we also eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Therefore, the detection of NSE serum levels could provide a laboratory basis for the clinical diagnosis of brain injuries . Kawle et al found that serum levels of NSE were an independent predictor of the outcome in IS patients . Furthermore, Smith et al showed that increased levels of NSE were correlated with brain infarction size, stroke severity, and overall prognosis …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the detection of NSE serum levels could provide a laboratory basis for the clinical diagnosis of brain injuries . Kawle et al found that serum levels of NSE were an independent predictor of the outcome in IS patients . Furthermore, Smith et al showed that increased levels of NSE were correlated with brain infarction size, stroke severity, and overall prognosis …”
Section: Discussionmentioning
confidence: 99%
“…Acute ischemic stroke, a major cerebrovascular disease, is caused by vascular occlusion that decreases cerebral blood flow to an area of brain perfused by an occluded artery . Atherosclerosis is the main cause of AIS, and inflammatory responses are involved in endothelial dysfunction and propagation of atherosclerosis, contributing to ischemic brain injuries .…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is the leading cause of acquired neurological disability and the second leading cause of death worldwide, with incidences ranging from 400 to 800 people per 100 000 every year worldwide . In China, 2.5 million new stroke cases occur each year, and there are 7.5 million stroke survivors; approximately 15%‐30% of stroke survivors are left permanently disabled .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 It is seen in all age groups and is increasingly common in younger ages with huge economic costs in management. [2][3][4] It has been estimated that there will be more than 1.67 million stroke survivors in India by 2020. 5,6 One of the most common disabilities in stroke is upper limb dysfunction with eighty-five percent of the survivors reported to experience hemi paresis immediately after stroke, fiftyfive to seventy-five percent continue life with motor deficit which affects daily life and social life.…”
Section: Introductionmentioning
confidence: 99%